2018
DOI: 10.3390/nano8070498
|View full text |Cite
|
Sign up to set email alerts
|

Deformation Behavior of Foam Laser Targets Fabricated by Two-Photon Polymerization

Abstract: Two-photon polymerization (2PP), which is a three-dimensional micro/nano-scale additive manufacturing process, is used to fabricate component for small custom experimental packages (“targets”) to support laser-driven, high-energy-density physics research. Of particular interest is the use of 2PP to deterministically print millimeter-scale, low-density, and low atomic number (CHO) polymer matrices (“foams”). Deformation during development and drying of the foam structures remains a challenge when using certain … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
50
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 57 publications
(53 citation statements)
references
References 43 publications
3
50
0
Order By: Relevance
“…Other researchers, such as Liu et al, [30] observed similar axial shear stress in analogous regions along the interface of a printed log-pile structure and in a fully dense "top cap," which is comparable to the grip pieces printed in the present work. In addition, we also observe non-uniform shrinkage at the stitch line (marked by yellow arrows) as evidenced by the sudden noticeable change in gage width (Figure 2e,f ).…”
supporting
confidence: 87%
See 3 more Smart Citations
“…Other researchers, such as Liu et al, [30] observed similar axial shear stress in analogous regions along the interface of a printed log-pile structure and in a fully dense "top cap," which is comparable to the grip pieces printed in the present work. In addition, we also observe non-uniform shrinkage at the stitch line (marked by yellow arrows) as evidenced by the sudden noticeable change in gage width (Figure 2e,f ).…”
supporting
confidence: 87%
“…Figure 1 shows the gage sections of both low-and high-density samples, as well as the as-printed feature dimensions. [30,31,33] The effects of this shrinkage on the materials' functionality, however, can be widespread, and its impact on the mechanical integrity of the architected materials is still unknown. The 1) width and 2) length of the elliptical voxels for both sets of samples were determined to be 250 and 850 nm, respectively (Figure 1c,d).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…The E-field distribution of light in these structures can be calculated and examined indirectly, however, there are no tools to probe the field internally. Ideally, an optically thin detector has to be integrated inside 3D photonic lattices, e.g., made by state-of-the-art direct laser writing 3D nanolithography [22,23]. A photodetector which is weakly absorbing and has low dispersion (non-pertubing 3D photonic crystal) could be made using a graphene-on-membrane approach.…”
Section: Introductionmentioning
confidence: 99%